The Role of Customer Service in the Success of the Digital Marketing Plan in the Kingdom of Saudi Arabia - Alomairi, Abeer; Alzubaidi, Hawazin (The Arab Journal of Administration, 2023)
After the COVID-19 pandemic, it became important for organizations to focus on digital marketing through social media and websites, so this research examined how digital marketing can be improved through customer service management. Where the current research aims to know the role of customer service management in the success of digital marketing plans for bank customers in the Kingdom of Saudi Arabia, due to the increasing importance of customer service as an important factor in improving the efficiency of digital marketing and an essential indicator of the performance of institutions. To achieve this, a survey was applied in this study to collect primary data using a random sample of (203) customers of Al-Rajhi Bank in Saudi Arabia, then analyzed by SPSS. The results of the study confirmed the impact of communication on the success of digital marketing plans, and explained how communication is an important factor to anticipate marketing effectively. The result also indicated the impact of meeting customer needs and trust on the success of digital marketing plans. It also recommended that discussions and future studies in the field of digital marketing and its impact on project management.